Financing global development: The potential of trade finance - Clara Brandi; Birgit Schmitz (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The UN Conference on Financing for Development in Addis Ababa in July 2015 will pave the way for the implementation of the post-2015 development agenda. The Briefing Paper series “Financing Global Development” analyses key financial and non-financial means of implementation for the new Sustainable Development Goals (SDGs) and discusses building blocks of a new framework for development finance. Although international trade is an integral component of the conference in Addis Ababa, trade finance itself has not been taken into consideration. This omission represents a serious shortcoming because trade finance is essential to international trade, especially for developing countries with less developed national financial markets and limited access to international financial markets. Every trade transaction must be financed. The non-availability of trade finance may therefore become an obstacle to international trade that impedes sustainable development. As international trade is one of the most important driving forces for economic development in developing countries and emerging markets, the availability of trade financing is extremely important for sustainable development. In particular, the integration of small and medium-sized enterprises (SMEs) into international trade is essential for emerging markets and developing countries and promotes economic development in an especially effective and sustainable manner. Trading in intermediate products has now become more important than end product trading, since goods are primarily produced within global value chains; two thirds of international trade is based on trade with intermediary products. Participation in global value chains is therefore an important objective for developing countries. Empirical literature shows that countries which are strongly integrated into global value chains experience, on average, higher economic growth; however, frictions in finance represent one of the greatest obstacles to participation in global value chains. According to estimates from the Asian Development Bank (ADB) for 2013, the annual global gap in trade finance amounts to USD 1.6 billion. Increasing the availability of trade finance by 5% could raise production and the number of jobs by 2%. According to surveys of market participants, the financial crisis led to a huge decline in the supply of trade finance. And yet even after the crisis was resolved, the availability of trade finance remains a significant problem in emerging markets and developing countries. Surveys show that this is especially the case in Africa and Asia. The lack of development within the financial sector can pose a significant hurdle to international trade and prevent emerging markets and developing countries from integrating into the global trade system more effectively and taking advantage of trade benefits. For this reason trade financing should be an important building block of the future framework for development finance. For developing countries, it is particularly important to put the focus on strengthening both local and regional banking sectors as well as their international interlinkages and on improving the connection between trade finance and value chains in order to promote the integration of SMEs into the global economy, for example by strengthening the respective support programmes for Supply Chain Finance.
Keywords: 330; Handel und Investitionen; Agenda 2030